Occupational mental health of non-family members in family firms: Evidence from Pakistan - Khan, Khalid; e-Habiba, Umm-; Sabeen, Zara; Waseem, Muhammad (Frontiers in Public Health, 2022)
Family-owned firms display distinct dynamics as compared to other firms. Consequently, the outcomes and consequences of these dynamics are also expected to be different. The aim of this study was to explore the impact of perceived employee-organization psychological distance (EOPD) on the occupational mental health (OMH) of the employees. Considering the complexities associated with employee–employer relationship, the study also investigated how this relationship between PD and OMH might be mediated by psychological safety (PS) perceived by the employees. Furthermore, the study also included proactive personality (PP) as a potential moderator of the relationship between PD and OMH. Results using SEM and fsQCA show a partial mediation effect on psychological safety. The study contributes by examining the distinct nature of family firms and their impact on the mental health of non-family member employees. This study contributes to the family firm literature by adopting a novel methodological approach to unveil the complexity behind the relationship between employees and owner-employers of family firms.